2009
DOI: 10.1007/s12665-009-0282-3
|View full text |Cite
|
Sign up to set email alerts
|

Mobility and ecological risk assessment of heavy metals in surface sediments of Xiamen Bay and its adjacent areas, China

Abstract: Xiamen Bay (XMB) has received substantial loadings of pollutants from industrial and municipal wastewater discharged since the 1980s. To assess ecological risks and the current spatial changes of metal contaminants in bottom surface sediments, 12 samples were collected. Samples were subjected to a total digestion technique and analyzed by ICP-OES for Cu, Pb, Zn, Cr, and Cd, and by AFS for Hg and As. Among these metals, Zn had the highest values (68-268 mg kg -1 ), followed by Pb (27-71 mg kg -1 ), and lower co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(39 citation statements)
references
References 36 publications
3
34
0
2
Order By: Relevance
“…The classification is based on the strength of the bond between metals and the different geochemical fractions in sediments and the ability of metals to be released (Cai et al 2011) and enter into the food chain. The carbonate and exchangeable fractions are considered to be weakly bonded metals, which may equilibrate with the aqueous phase and become more rapidly bioavailability (Hseu 2006;Yan et al 2010). According to RAC, if the carbonate and exchangeable fractions are lower than 1 %, there is no risk for the aquatic system, low risk for a range of 1-10 %, medium risk for a range of 11-30 %, and high risk for a range of 31-50 %, and higher than 50 % is considered very high risk (Yan et al 2010).…”
Section: Ecological Risk Assessmentmentioning
confidence: 99%
“…The classification is based on the strength of the bond between metals and the different geochemical fractions in sediments and the ability of metals to be released (Cai et al 2011) and enter into the food chain. The carbonate and exchangeable fractions are considered to be weakly bonded metals, which may equilibrate with the aqueous phase and become more rapidly bioavailability (Hseu 2006;Yan et al 2010). According to RAC, if the carbonate and exchangeable fractions are lower than 1 %, there is no risk for the aquatic system, low risk for a range of 1-10 %, medium risk for a range of 11-30 %, and high risk for a range of 31-50 %, and higher than 50 % is considered very high risk (Yan et al 2010).…”
Section: Ecological Risk Assessmentmentioning
confidence: 99%
“…In the majority of studies (e.g., Ebrahimpour & Mushrifah 2008;Singh et al 2008;Marcovecchio et al 2010;VillalobosCastañeda et al 2010;Yan et al 2010), toxic metals have mostly been found bound to the reducible and residual phase. However in this study, toxic metals including Mo, Zn, Pb, Cd, and Cu were strongly bound to the watersoluble or exchangeable phase in surficial Lake Kalimanci sediments, representing a major threat for the inhabitants of a large part of Makedonska Kamenica.…”
Section: Cobalt (Co)mentioning
confidence: 99%
“…Therefore, investigating the distribution of Hg in coastal sediments is an effective way to understand the translocation and cycling of Hg, and to reconstruct the chronology of anthropogenic Hg emissions at the land-ocean interface zone. Some efforts have been made to study the contamination of Hg in sediments from several specific estuaries and coastal regions of China, including Bohai Sea, East China Sea, Xiamen Bay, Pearl River Estuary and Hong Kong (Fang and Chen, 2010;Gu et al, 2012;Luo et al, 2010;Yan et al, 2010;Zhou et al, 2007). However, the behavior of Hg may differ from one estuary to another due to the various inputs, physical, chemical and hydrological conditions.…”
mentioning
confidence: 99%